Unveiling The Phytochemical Richness, Antioxidant Potential, And Shelf-Life Stability of Multi-Herbal Powder Incorporated Tea - S, Aariba; Raman, Meera (Journal of Neonatal Surgery, 2025)
This study evaluated the phytochemical composition, antioxidant potential, and shelf-life stability of multi-herbal powder incorporated tea (MHT) formulations (MHT1 to MHT4) in comparison to a control. Quantitative phytochemical analysis revealed substantial enhancements in key bioactive compounds, with alkaloid content increasing from 12±0.01 mg/100g in the control to 25±0.1 mg/100g in MHT4, saponin levels rising from 8±0.02 mg/100g to 21±0.3 mg/100g, and tannin content from 10±0.03 mg/100g to 23±0.2 mg/100g. These increases reflect the diverse phytochemical profiles contributed by the herbal blends, known for their antioxidant, anti-inflammatory, and antimicrobial properties. Antioxidant assays further confirmed this enhancement, with total phenolic content rising from 56.63±1.56 mg/100g to 80.27±0.61 mg/100g and flavonoid content from 19.07±1.46 mg/100g to 35.17±0.91 mg/100g, indicating stronger radical scavenging capacity. MHT4 consistently demonstrated the highest antioxidant activity, as indicated by DPPH (IC₅₀: 79.24±0.21 µg/ml), ABTS (98.24±0.21 µg/ml), and FRAP (87.13±1.01 µg/ml) assays. Shelf-life studies revealed that MHT2 exhibited the lowest microbial counts at the 30th day (2.01 x 10⁶ CFU/g TPC, 1.75 x 10⁵ CFU/g fungal count), suggesting better long-term stability. These findings indicate that MHT formulations, particularly MHT4, offer substantial health benefits as functional beverages, with rich phytochemical profiles, strong antioxidant activity, and promising shelf stability. However, further optimization is recommended to enhance microbial resistance and extend commercial viability. Future research should focus on clinical validation and sensory evaluations to fully assess the therapeutic potential and consumer acceptability of these formulations